Identification of immune-related genes for Hepatocellular Carcinoma: a study based on TCGA data - Chun-Bo Li; Hui-Feng Wang; Zheng-Kai Feng; Yu-Bin Fu; Jian Zhang; Jing-Yi Qin (Journal of Men's Health, 2021)
Background and objective: Hepatocellular Carcinoma (HCC) is frequently diagnosed at the advanced stage and current treatment methods are marginally effective. The immune system is critical for the development of HCC. However, the interplay between the immune system and HCC is not well illustrated. Hence, the aim of our work was to investigate the relationship between HCC and the abnormal immune gene expression to study the potential mechanism. Material and methods: We downloaded RNA-seq data from TCGA database, identified differentially expressed genes (DEGs) using the edgeR package, and overlapped DEGs and immune-related genes from the InnateDB website to obtain immune-related DEGs. After survival analysis, the immune-related DEGs that were significantly related to prognosis were analyzed by the STRING tool to construct PPI network. The genes in two significant PPI network modules identified by MCODE plugin were investigated by functional enrichment analysis and tumor-infiltration analysis. Results: 68 immune-related DEGs were found to be significantly associated with prognosis in HCC, and then a PPI network was constructed. The genes in two significant PPI network modules were enriched in 31 biological processes of GO (e.g. regulation of complement activation, extracellular matrix disassembly) and 12 KEGG pathways (e.g. complement and coagulation cascades, cell cycle, proteoglycans in cancer), which were highly involved in HCC. Furthermore, we obtained 7 genes whoes expressions were significantly associated with immune infiltration levels, including E2F1, PLK1, MMP9, CDKN2A, BIRC5, CCNA2 and DCN, and 8 genes whoes copy number variations were significantly related to immune cell infiltrations, including C8A, C8B, E2F1, C6, C7, BIRC5, CCNA2 and CFB. Conclusions: These findings contribute to understand the mechanism of HCC and provide a direction for further research on the immunotherapy of HCC.